Impact of H‐Doping on n‐Type TMD Channels for Low‐Temperature Band‐Like Transport. Issue 38 (4th August 2019) - Lee, Han Sol; Park, Sam; Lim, June Yeong; Yu, Sanghyuck; Ahn, Jongtae; Hwang, Do Kyung; Sim, Yumin; Lee, Je‐Ho; Seong, Maeng‐Je; Oh, Sehoon; Choi, Hyoung Joon; Im, Seongil
Abstract: Band‐like transport behavior of H‐doped transition metal dichalcogenide (TMD) channels in field effect transistors (FET) is studied by conducting low‐temperature electrical measurements, where MoTe2, WSe2, and MoS2 are chosen for channels. Doped with H atoms through atomic layer deposition, those channels show strong n‐type conduction and their mobility increases without losing on‐state current as the measurement temperature decreases. In contrast, the mobility of unintentionally (naturally) doped TMD FETs always drops at low temperatures whether they are p‐ or n‐type. Density functional theory calculations show that H‐doped MoTe2, WSe2, and MoS2 have Fermi levels above conduction band edge. It is thus concluded that the charge transport behavior in H‐doped TMD channels is metallic showing band‐like transport rather than thermal hopping. These results indicate that H‐doped TMD FETs are practically useful even at low‐temperature ranges. Abstract : The impact of H‐doping on n‐type transition metal dichalcogenide (TMD) channels for low temperature band‐like transport is demonstrated. As H‐doped by atomic layer deposition, TMD channels show strong n‐type and their mobility increases with temperature lowering, while the mobility of unintentionally doped TMD field effect transistors always drops at low temperatures. Density functional theory calculations shows that H‐doped TMD channels have Fermi levels above conduction band edge.